Weak Lefschetz property of graded Gorenstein algebras associated to the Apéry set of a numerical semigroup - Tran, Quang Hoa; Ho, Vu Ngoc Phuong (Hue University Journal of Science: Natural Science, 2021)
It has been conjectured that all graded Artinian Gorenstein algebras of codimension three have the weak Lefschetz property over a field of characteristic zero. In this paper, we study the weak Lefschetz property of associated graded algebras A of the Apéry set of M-pure symmetric numerical semigroups generated by four natural numbers. These algebras are graded Artinian Gorenstein algebras of codimension three.